A conjugate protein containing HIV TAT, ISG20, and a PRRSV polymerase binding inhibits PRRSV replication and may be a novel therapeutic platform. (August 2017) - Liu, Ke; Li, Yuming; Zhou, Bin; Wang, Feifei; Huan, Beili; Shao, Donghua; Wei, Jianchao; Qiu, Yafeng; Li, Beibei; Qian, Yingjuan; Jung, Yong-Sam; Miao, Denian; et al.
Abstract: Porcine Reproductive and Respiratory Syndrome (PRRS), which is caused by Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) infection, has caused substantial economic losses for the global swine industry. To date, there are limited commercially available measures to control the spread of PRRSV. The available vaccines are unstable and there is no anti-PRRSV therapeutic available. Therefore, this study designed a novel recombinant antiviral protein that included a novel polypeptide that binds to the PRRSV polymerase (p9), the transduction ability of the HIV TAT, and the nucleotide degradation activity of interferon stimulated gene 20 (ISG20). The recombinant proteins TAT-p9-ISG20 and p9-ISG20 were expressed in MARC-145 cells by transient transfection and then tested for antiviral activity and entry efficiency. The p9-ISG20 construct had greater antiviral activity than either p9 alone (1.37-fold) or ISG20 alone (1.9-fold). Addition of the HIV TAT protein increased the entry efficiency of p9-ISG20 by 1.57-fold, which was associated with increased anti-viral activity (1.52-fold) compared to P9-ISG20. In summary, TAT-p9-ISG20 achieved a synergistic effect by combining three different antiviral proteins and may be a novel PRRSV therapeutic platform. Highlight: Combine ISG20 and viral polymerase binding peptide as new antiviral agent Specific bind and inhibit PRRSV polymerase Combine protein showed higher antiviral activity than single.